Primary Angiitis of the Central Nervous System: From Psychiatry to Neurology - Joel Leonardi; Christian Saleh; Phillip Jaszczuk; Kristine A. Blackham; Sabrina Zechel; Stefanie Wilmes; Margret Hund-Georgiadis (Case Reports in Neurological Medicine)
We present a case of a 54-year-old man with primary angiitis of the central nervous system (PACNS) who was initially admitted to a psychiatric clinic with a diagnosis of delirium. We discuss the difficulty in establishing the diagnosis of PACNS and provide the reader with some recommendations on how to promptly and correctly diagnose this disease in order to avoid potentially lethal outcomes.